(3GdbUjOI GdaGFMI aj JLhjO GdaGJMI hTQMgGs - (3eMeO Hf eMehO Hf eMeO Hf CMeO, TeS GdOjf GdSeQbfOj,J (B780 (3g` s
(3ChdgG (B:s
(3HMeO GdGdg GdeSJYGf JhSdG hHGdUdGI GdRGcjGJ JhUdG Ydi GdeUWai GdgGOi GdTajY hBdg hSde Ydi GUMGHg UGMHi GdYdG s
(3BNQgG (B:s
(3hbO PcQfG ai QhM GdeQjO ai TQM GdYbO GdaQjO ai fXe GdJLhjO HjGfkG cGajkG hGddg GYde s
(3Vef eLehY , JQJjHgG (B: (3GdJGSY hGdKdGKhfs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3fXe GdeDda GdbUjOI hTQMgG eYkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B4s
Keywords: (3GdbQGAGJ hGdJLhjOs